Secure Full-Text Retrieval on Cloud - Deepthi, B.; ., Rakesh (International Journal of Engineering and Technology, 2018)
Cloud Computing is a present day technology that effectively support the client oriented services. These days we are mostly using applications that consumes the cloud storage for storing and retrieving information. In such case that data management and privacy preservation cryptographic technique the data is converted to unreadable format. Due to this full text retrieval on encrypted data on cloud of required information becomes complex. Therefore in this paper we proposed bit slice indexing method on Elliptic-Curve-Diffie-Hellman for providing some security to cloud.